Microwave Curing Effect on Internal Sulphate Damage in Nano Alumina Reinforced White Cement - Gülteki̇n, Arzuhan Burcu; Kaplan, Gökhan; Kiliç Demi̇rcan, Rüya; Çakmak, Coşkun (IOP Publishing, 2019)
In this study, microstructural investigation was carried out to analyse the internal sulphate damage in the nano-Al2O3 (nAl) reinforced white cement pastes. As white cement is generally used in the production of architectural concrete, 52.5 R type white cement was preferred in the scope of the study. Nano Al2O3 was substituted into the cement paste at 0% and 5% ratios. Three different methods were used for microwave curing. Different microwave curing techniques were performed as 120 minutes of 100 Watt application, 75 minutes of 100 Watt-30 minutes of 150 Watt-15 minutes of 200 Watt application, and 90 minutes of 100 Watt-15 minutes of 150 Watt-15 minutes of 200 Watt. In order to accelerate the formation of DEF damage, Na2SO4 was added to the cement paste at 2%, and 5% ratios. Three different microwave curing methods were used to investigate the occurrence of DEF damage in nano Al2O3 reinforced concrete concretes. In the pastes produced for this purpose, dense ettringite structure was observed. In cement pastes without nAl, the ettringite structure had a low S / Ca ratio (<0.20). More ettringite was formed in methods 2 and 3 used as microwave curing. The heat treatment applied in the microwave curing was the same as in other thermal curing applications, and in case the inner sulphate source was present it led to the formation of ettringite. This process became more evident in the presence of NA by increasing power application